Constitutive Phosphorylation as a Key Regulator of trpm8 Channel Function - Madrid-Montecinos, R; Rivera-Bravo, B; Pertusa-Pastor, M; Moreno-Pohl, C (Society for Neuroscience, 2021)
In mammals, environmental cold sensing conducted by peripheral cold thermoreceptor neurons mostly depends on TRPM8, an ion channel that has evolved to become the main molecular cold transducer. This TRP channel is activated by cold, cooling compounds, such as menthol, voltage, and rises in osmolality. TRPM8 function is regulated by kinase activity that phosphorylates the channel under resting conditions. However, which specific residues, how this post-translational modification modulates TRPM8 activity, and its influence on cold sensing are still poorly understood. By mass spectrometry, we identified four serine residues within the N-terminus (S26, S29, S541, and S542) constitutively phosphorylated in the mouse ortholog. TRPM8 function was examined by Ca21 imaging and patchclamp recordings, revealing that treatment with staurosporine, a kinase inhibitor, augmented its cold- and menthol-evoked responses. S29A mutation is sufficient to increase TRPM8 activity, suggesting that phosphorylation of this residue is a central molecular determinant of this negative regulation. Biophysical and total internal reflection fluorescence-based analysis revealed a dual mechanism in the potentiated responses of unphosphorylated TRPM8: A shift in the voltage activation curve toward more negative potentials and an increase in the number of active channels at the plasma membrane. Importantly, basal kinase activity negatively modulates TRPM8 function at cold thermoreceptors from male and female mice, an observation accounted for by mathematical modeling. Overall, our findings suggest that cold temperature detection could be rapidly and reversibly fine-tuned by controlling the TRPM8 basal phosphorylation state, a mechanism that acts as a dynamic molecular brake of this thermo-TRP channel function in primary sensory neurons. © 2021 Society for Neuroscience. All rights reserved.